2017
DOI: 10.3847/1538-4357/aa6194
|View full text |Cite
|
Sign up to set email alerts
|

Long-slit Spectroscopy of Edge-on Low Surface Brightness Galaxies

Abstract: We present long-slit optical spectra of 12 edge-on low surface brightness galaxies (LSBGs) positioned along their major axes. After performing reddening corrections for the emission-line fluxes measured from the extracted integrated spectra, we measured the gas-phase metallicities of our LSBG sample using both the In the luminosity-metallicity plot, our LSBG sample is consistent with the behavior of normal galaxies. In the mass-metallicity diagram, our LSBG sample has lower metallicities for lower stellar mass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…In this work we have, for the first time, investigated the effect of environment on the fraction of metals lost from galaxies. In addition to reproducing the trend of lower mass galaxies losing more metals seen in both observational and theoretical works (Dalcanton 2007;Ma et al 2016;Du et al 2017), we make several predictions, which are summarised below:…”
Section: Discussionmentioning
confidence: 80%
“…In this work we have, for the first time, investigated the effect of environment on the fraction of metals lost from galaxies. In addition to reproducing the trend of lower mass galaxies losing more metals seen in both observational and theoretical works (Dalcanton 2007;Ma et al 2016;Du et al 2017), we make several predictions, which are summarised below:…”
Section: Discussionmentioning
confidence: 80%
“…The remaining designations are the same as those on the left panel. The red crosses on both panels indicate the characteristics of LSB galaxies from Du et al (2017).…”
Section: Analysis Of the Colorsmentioning
confidence: 99%
“…4 indicate the characteristics of edge-on LSB galaxies from Du et al (2017). These galaxies have metallicities, luminosities, and sizes comparable to those of SDSS J170745+302056.…”
Section: Analysis Of the Colorsmentioning
confidence: 99%
“…Since B band is more sensitive to the star formation, such selection of the LSBG sample may cause a bias for the galaxy population with a diffuse star formation structure. Moreover, an average LSBG has a relatively young stellar population and low metallicity (Du et al 2017). The typical stellar mass is much lower than the M * at the similar redshift (Du et al 2020), indicating an early forming stage of the galaxies.…”
mentioning
confidence: 96%
“…So the wide field HI survey projects such as ALFALFA (Haynes et al 2011(Haynes et al , 2018, combined with SDSS optical images, would provide us optimal means to obtain a large sample of LSBGs with reliable HI redshift. Our previous series study based on the LSBGs selected from ALFALFA sample with optical surface brightness measured from SDSS images (Du et al 2015;He et al 2019;Du et al 2019) have shown that the LSBGs have much lower metallicity (Du et al 2017), follow the Tully-Fisher relation (Du et al 2019), and have similar mass-light ratios to the high surface brightness galaxies (Du et al 2020). The Hα images of our HI selected LSBG sample also shows that the star formation surface density has a very weak correlation with the gas surface density, the star formation surface density is much lower than the prediction of Kennicutt-Schmidt law (Kennicutt 1998;Kennicutt & Evans 2012), leading to a significantly longer gas depletion time scales, and low star formation efficiency (Lei et al 2018(Lei et al , 2019.…”
mentioning
confidence: 99%